Water mites of the genus Brachypoda Lebert, 1879 (Acari: Hydrachnidia: Aturidae) from South Korea and the Russian Far East - Pešić, Vladimir; Semenchenko, Ksenia (Zootaxa, 2014)
In this study, four water mites of the genus Brachypoda (Acari: Hydrachnidia: Aturidae) are reported from South Korea and the Far East of Russia. Brachypoda (Ocybrachypoda) milicaae sp. n. (South Korea), B. (Ocybrachypoda) sokolowi sp. n. (Russia) and B. (Eubrachypoda) rossica sp. n. (Russia) are described as new for science. The latter species is the second representative of the subgenus Eubrachypoda Tuzovskij, 2004, previously known only from Lake Biwa in Japan. A new record of Brachypoda rubidata Kim & Chung, 1996, a species so far known only from a pond in Bosung (South Korea), is given.